2019
DOI: 10.1080/09637486.2019.1686752
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dietary glycemic index and glycemic load in pregnant women and risk for gestational diabetes mellitus

Abstract: The risk of gestational diabetes mellitus (GDM) increases during the second trimester of pregnancy. However, the role of dietary glycemic index (GI) and glycemic load (GL) on GDM risk is controversial. We aimed to determine the association of established risk factors of GDM with GI and GL among healthy pregnant women, and whether GI and GL were subsequently related to GDM risk. Dietary GI and GL were assessed in healthy pregnant women from the Seremban Cohort Study using a food frequency questionnaire. After a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Of the 124 items found from the database and internet search, we included 15 publications in the qualitative analysis (Basri et al 2018;Gill et al 2012;Goh et al 2018;Hasbullah et al 2020;Idris et al 2009;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Kampan et al 2013;Logakodie et al 2018;Muniswaran et al 2017;Nordin et al 2006;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007. Two publications with low quality score were excluded (lack of information on the patient recruitment and diagnostic method) (Goh et al 2018;Muniswaran et al 2017).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 124 items found from the database and internet search, we included 15 publications in the qualitative analysis (Basri et al 2018;Gill et al 2012;Goh et al 2018;Hasbullah et al 2020;Idris et al 2009;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Kampan et al 2013;Logakodie et al 2018;Muniswaran et al 2017;Nordin et al 2006;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007. Two publications with low quality score were excluded (lack of information on the patient recruitment and diagnostic method) (Goh et al 2018;Muniswaran et al 2017).…”
Section: Search Resultsmentioning
confidence: 99%
“…Two publications with low quality score were excluded (lack of information on the patient recruitment and diagnostic method) (Goh et al 2018;Muniswaran et al 2017). Eleven publications provided prevalence data (Basri et al 2018;Gill et al 2012;Hasbullah et al 2020;Idris et al 2009;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Logakodie et al 2018;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007. Four publications provided risk factors data (Gill et al 2012;Shamsuddin et al 2001;Tan et al 2012Tan et al , 2007, and seven publications provided maternal, foetal/neonatal complications data (Basri et al 2018;Ismail et al 2013Ismail et al , 2011Kalok et al 2018;Kampan et al 2013;Logakodie et al 2018;Nordin et al 2006).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruits also contain dietary fibre, which affects the GI and GL. A recent study suggested that although GI and GL were not significantly associated with the risk of GDM, higher GI and GL were associated with lower fibre intake, which may be a risk factor for GDM (44) . Furthermore, previous studies have shown that pre-pregnancy fruit fibre intake may lower the risk of GDM (41,45) , and a recent study suggested that a dietary pattern characterised by high fibre may lower the GDM risk (46) ; however, evidence regarding whether dietary fibre intake during pregnancy influence the risk of GDM is still lacking.…”
Section: Discussionmentioning
confidence: 95%
“…13 A small body of evidence on glycemic index, glycemic load, and dietary fiber intake in early pregnancy in relation with GDM risk is inconsistent and most studies suggest no association. [14][15][16][17] Vitamin D status has received more attention, and a meta-analysis summarizing evidence from 10 observational studies has found that low maternal concentrations of 25(OH) D during early pregnancy were associated with a higher risk of GDM (odds ratio [OR]: 1.49, 95% confidence interval [CI]: 1.18-1.89). 18 However, it remains unclear if higher early pregnancy vitamin D intake from foods or supplements is associated with GDM risk.…”
Section: Dietary Factorsmentioning
confidence: 99%